A Grave Cross on Eastern-Slavonic Ritual Towels: Life and Death on Textiles - Brovarets, Tetiana (Eikón / Imago, 2021)
The paper presents Eastern-Slavonic rushnyks (embroidered towels with a sacral meaning) with the images of death. Despite the fact that the origin of them was printed cross-stitch papers, these images became folklorized, as there have been many transformations in folk culture (both formal and mental). The aim of the article is to show different understandings of one and the same picture (a grave cross with guelder roses twigs wrapped around it and two birds sitting against each other on the twigs) and the typical inscription (“My grave is under the cross; my love is on the cross”) to it. This is possible by analyzing various combinations of mentioned visual and verbal formulas with others that were also embroidered on rushnyks in conjunction with the previous ones. The author makes the conclusion that hanging on the walls, Eastern-Slavonic embroidered towels with such formulas presented, for the most part, memento mori topic, demonstrating various forms and manifestations of passing away.